Studi Living Hadis terhadap Tradisi Syawalan di Masjid Al Haq Karangploso Yogyakarta - Alkhairi, Aulia Azmi; Hidayah, Ahwil Lutan; Nida, Sofwatun; Marhumah, Marhumah (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
This research is based on the phenomenon of community diversity in Karangploso, Maguwoharjo in the momentum of the month of Shawwal after Eid al-Fitr. This research aims to understand the Syawalan tradition in Al Haq Mosque, Karangploso, Maguwoharjo Village, Sleman, Yogyakarta which includes the meaning, application of hadith, and its impact on the strengthening of Islamic ukhuwah and social life of the community. The research method used is qualitative with a phenomenological approach. The data collection technique was carried out through participant observation and interviews with mosque administrators. The results of the study show that (i) the Shawwalan tradition at the Al Haq Mosque has spiritual, social, and cultural meaning; (ii) The application of hadith in the Syawalan tradition can be seen in the delivery of religious tausyiah, eating together, and reciting the Syawalan pledge; (iii) The positive impact of the Syawalan tradition is the creation of good relations between the community and mosque worshippers, strengthening the relationship between others, and creating an atmosphere full of happiness and togetherness.